TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENCURIAN YANG DILAKUKAN ANAK DI BAWAH UMUR DALAM PUTUSAN PENGADILAN NEGERI BANGKINANG KELAS IB NOMOR: 8/PID.SUS/ANAK/2019/PN.BKN - Pardi, Ahmad; Syahrial, Syahrial; Saputra, Rian Prayudi (Pahlawan Tuanku Tambusai University, 2022)
Child protection is an effort to provide conditions where every child can carry out his rights and obligations. Judging from the age level, criminal acts that occur in society are not only committed by the adult age group. But those who are children often commit criminal acts. The formulation of the problem in this study is whether there is legal protection for minors as perpetrators of the crime of theft in decision number: 8/pid.sus/anak/2019/pn.bkn and analysis of evidence for the judge's consideration in the trial of Decision Number: 8/Pid.Sus/Children/Pn.No. The method used is normative juridical. The results obtained are the implementation of legal protection against perpetrators of criminal acts of theft committed by minors. As well as what kind of protection will be given to perpetrators of criminal acts of theft by minors. The second is that cases involving children, especially in Decision Number: 8/pid.sus/anak/2019/pn.bkn, are better resolved out of court because the nominal value of the goods taken is only small in the Circular Letter of the Supreme Court concerning losses below 2.5 million cannot be held according to Supreme Court Regulation Number 2 of 2012. Keywords: Juridical Review, Crime of Theft, Children